Kecemasan Pada Penderita Kanker - Fauziah, Reissa Nur; Wisnu Sri Hertinjung., M.Psi, Psi, Wisnu Sri Hertinjung., M.Psi, Psi (2016)
In Indonesia, cancer representing one of the disease type killings where this disease could be groans whosoever do not know the social class of economics, gender and patient age. In world estimated by 7,6 million people die effect of cancer in 2005 and 84 million one would die till 10 year forwards (WHO, 2005). Cancer disease could be because the mortality estimated will be continued to increase. This matter that's making this disease resides in sequence to 6 death cause. Pursuant to the mentioned, cancercous oftentimes generate the feeling worry to death for every one who hears it. Taylor (1998) dread was an experience subjective of concerning mental stress fidgeting as public reaction and disability face the problem or inexistence feel safe. Therefore researcher interested to study the anxiety at cancer patient. Researcher was use qualitative method with the research informan consisted by 3 especial informan and 3 supporter informan. Especial informan was patient of cancer patient with the adult age early, madya adult and final adult, while supporter informan was one who always consorts the especial informan during cancercous medication process. In this research, researcher was use the interview and observation method as a means of data compiler. Result from this research indicate that the step of cancer patient when confronted with death between individual one individually was other differences, do not was regularly passed by and just earn skipped over was swiftly depended from patients psychical condition. There were two factor influencing cancer patients in face of dread to death that was internal factor and factor external. Internal factor cover the age of cancer patient, while factor external covers the education background, cancer stadium, nuptials status, old suffer the social support and cancer. Dread of at the cancer patients and factors influencing it each other interconnected one another. So that, knowable of dread influenced by patients psychical condition, and also background by some internal and external factor was each itself individual.